2015
DOI: 10.1177/0022034515618959
|View full text |Cite
|
Sign up to set email alerts
|

Light-Cured Self-Etch Adhesives Undergo Hydroxyapatite-Triggered Self-Cure

Abstract: Light cure is a popular mode of curing for dental adhesives. However, it suffers from inadequate light delivery when the restoration site is less accessible, in which case a self-cure mechanism is desirable to salvage any compromised polymerization. We previously reported a novel self-cure system mediated by ethyl 4-(dimethylamino)-benzoate (4E) and hydroxyapatite (HAp). The present work aims to investigate if such self-cure phenomenon takes place in adhesives that underwent prior inadequate light cure and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…However, the phosphate peak intensity was lower, and carbonyl stretching (1,720 cm −1 ) peaks were also observed at a greater depth with both BMEP15 and BMEP40 at the resin-dentine interface compared to CFSE, indicating greater demineralization and deeper ingress. Similar observations have been reported on model systems of BMEP and EDAB with HA ( Zhang and Wang 2012a , 2012b ; Liu et al 2016 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…However, the phosphate peak intensity was lower, and carbonyl stretching (1,720 cm −1 ) peaks were also observed at a greater depth with both BMEP15 and BMEP40 at the resin-dentine interface compared to CFSE, indicating greater demineralization and deeper ingress. Similar observations have been reported on model systems of BMEP and EDAB with HA ( Zhang and Wang 2012a , 2012b ; Liu et al 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…3C ). Earlier studies by Liu et al (2016) also reported a secondary cure of BMEP via chemical initiation, which enhanced degree of cure within similar systems using FTIR and Raman line mapping. Time-resolved FTIR spectra of 10-MDP–HA interaction reported similar findings, the process being dependent on concentration of HA and acidity of the monomer ( Liu and Wang 2019 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previously we reported a very unique spontaneous polymerization phenomenon of bis [2-(methacryloyloxy)ethyl] phosphate (2MP) mediated by ethyl 4-(dimethylamino)benzoate (4E) and hydroxyapatite (HAp) [21,22]. This new initiation system induced self-cure of 2MP monomer at low pH and could be a good solution to dual-cure of acidic self-etch adhesives [23]. However, although the two phosphate groups of 2MP could offer strong capability of etching, there have been few studies reporting the application of 2MP as a selfetching monomer.…”
Section: Introductionmentioning
confidence: 99%
“…As biocompatible filler, hydroxyapatite (HAP) is attractive due to its similarity to human bone and teeth; however, HAP is characterized by a hydrophilic surface which prevents dispersion and adhesion with hydrophobic polymeric matrices, thus affecting the overall performance of composites. Coupling agents capable to promote the adhesion of HA with a polymer matrix can slow the HA degradation process, protect the filler against fracture, increase the resistance to hydrolytic degradation of composite, and improve the stress distribution at the interface between the flexible organic matrix to the stiffer inorganic filler particles . Along with the incorporation of ceramic fillers for improved mechanical properties, the incorporation of antimicrobial agents in dental restoration materials is of clinical importance.…”
Section: Introductionmentioning
confidence: 99%